New generation open-bite treatment with zygomatic anchorage - (:unkn) unknown (E H ANGLE EDUCATION RESEARCH FOUNDATION, INC, 2006)
This technical note aims to present the fabrication and application of a new generation of posterior intrusion appliances using zygomatic anchorage. The use of zygomatic anchorage enables en masse impaction of the posterior segment without any side effects such as labial flaring. A 14-year-old, female Class II patient with an anterior open bite was treated with a new generation posterior intrusion appliance. At the end of treatment, a Class I canine and molar relationship and a correction of the anterior open bite were achieved. The molars were impacted 3.6 mm, and this impaction was maintained throughout the treatment. The mandibular plane showed a counterclockwise autorotation of 4 degrees. This case report demonstrates that zygomatic anchorage can be used effectively for molar intrusion and anchorage maintenance. However, further clinical studies with larger samples are required to confirm its effectiveness.
Keywords: zygomatic anchorage; implant anchorage; open-bite treatment; CEPHALOMETRIC EVALUATION; ENDOSSEOUS IMPLANTS; SKELETAL ANCHORAGE